A study on complications in land mark technique catheterization of internal jugular vein - KS, Henjarappa; Havaldar, Pavan P.; Shaik, Hussain Saheb (International Journal of Research in Medical Sciences, 2017)
Background: The traditional methods of using anatomic landmarks to guide cannulation of the IJV have yielded various rates of successful access and complications. Moreover, central venous catheterization requires considerable expertise. Cannulation of the IJV was first described in 1969. Various positions were used to access cannulation but they were frequently associated with complications such as arterial puncture, pneumothorax, neurological damage, infection, dysrhythmias, atrial thrombus, cardiac rupture. Methods: Thirty critical care patients were selected for IJV cannulation either by Land mark technique. This study conducted in department of anaesthesiology and critical care, M. S. Ramaiah medical college, Bangalore. India. Results: In our study there was 83.3% success in LMG technique. The mean access time was 323.23 ± 146.19 sec and the distribution of complications encountered during the study, Carotid artery was accidentally punctured in 1 (3.3%) cases. In LMG technique, there were no cases of arrhythmias, haematoma, pneumothorax, haemothorax, nerve injury and catheter malposition were noted during the study. Conclusion: Land mark technique catheterization of internal jugular vein was shown complications than newly developed ultrasound guided method.